Breaking Away from the Textbook: Creative Ways to Teach World History - Pahl, Ron H. (Rowman & Littlefield Publishers, 2011)
Teaching history should not simply be an endless recitation of irrelevant facts, entombed between the covers of a textbook. Instead, Breaking Away from the Textbook offers a fascinating journey through world history. Not a comprehensive, theory-heavy guide, this book instead focuses on exciting classroom activities, methods for students to grapple with human issues, and innovative ways to show students the relevance of the past to the world today. Simply put, this book makes world history fun. Soon your students will be busy debating, thinking, applying, and learning about information that will stay with them for a lifetime. The key to this wonderful work is that it incorporates various disciplines including art, music, and writing to create a vibrant classroom. Volume I covers prehistory to the Renaissance and Volume II covers the Enlightenment to the 20th century. Includes pictures and drawings, appendices, indexes, maps, and a bibliography. Volume III: More Creative Ways to Teach World History covers ancient times through the 20th century and beyond. Appropriate for all grade levels.